Dual-Source-CT coronary angiography for predicting success of revascularization in chronic total occlusions - S.D. Reinartz; S. Reith; R. Koos; K.M. Sucigan; C.K. Kuhl; A.H. Mahnken (Вестник рентгенологии и радиологии, 2016)
Objective. 25 consecutive patients underwent cardiac CT between November 2009 and September 2012 to evaluate configuration of chronic total occlusion (CTO) of a coronary artery to assess eligibility of percutaneous recanalization. Material and methods. Between 11/2009 and 06/2014 25 consecutive patients underwent DSCT-CA for evaluation of CTO. Technical success and complication rate of revascularization procedures were documented. For image analysis the datasets of 12 parameters were used to calculate CTO-try score. By calibration to the study cohort the AC-CTO-try and simplified CTO-try score were constructed respectively and compared to J-CTO by the area under the ROC-curve. Results. 88% of CTOs involved the right coronary artery (RCA) with a mean length of 4.6 ± 2.7 cm. 68% (17/25) were stratified as difficult or very difficult CTO-segments by J-CTO. Based on CTO-try an intervention was recommended in 9/25 patients, while revascularization was attempted in 16/25 (64%) patients with a success rate of 56% (n = 9/16). Negative predictive value for revascularization failure was 75%. By using sCTOtry, discrimination between success and failure of the intervention was measured with an AROC = 0.892. Conclusions. DSCT-CA permits visualization of the occluded vessel segment and provides a tool for assessing the probability of revascularization failure based on the CTO-try score. SCTOtry, calibrated to our cohort and expertise, can be used for predicting success of recanalization attempt.